META-ANALISIS KEEFEKTIFAN MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA SD - Moh Rifai, Nyoto Hardjono (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The purpose of this research is to analyze the effectiveness of the Student Team Achievement Division (STAD) model in improving social studies learning outcomes of elementary school students. This model is one type of cooperative learning that can increase students’ learning motivation. First, the researcher formulated the research problem and then collected existing research data that had been published through Google Scholar. The research data consisted of 12 journal articles and 1 relevant thesis. The researcher analyzed the results of the studies using quantitative comparative methods. Based on the results of the analysis, the Student Team Achievement Division (STAD) model is effectively used to improve social studies learning outcomes of elementary school students. The increase in elementary students’ learning outcomes ranged from the lowest increase of 6.9% to the highest increase of 56.6%, with an average increase of 34.61%. Keywords: , elementary school